MATHEMATICAL MODEL OF THE STATIC MODE OF THE LOW-TEMPERATURE SEPARATION PROCESS - Horbiychuk, Mykhailo; Yednak, Ihor (European Science, 2024)
The gas extracted from the well contains impurities - oxygen, nitrogen, hydrogen sulfide, as well as condensate, heavy hydrocarbons, butane, propane and their derivatives. Before the gas is sent to consumers, it is cleaned. The gas purification process pr